Hunter killer [compact disc, unabridged] - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller., 2020)
While Pike Logan and Jennifer Cahill prepare to join the Taskforce on a counter-terrorist mission, a vicious explosion kills a friend, and Pike knows the attack was meant for him.